Teoria funcionalista dos valores humanos: testando sua adequação intra e interculturalmente - Medeiros, Emerson Diógenes de (2011)
This thesis aimed at knowing the adequacy of the functional theory of human values in the ambit within and between cultures. Specifically, the content and structure of values proposed by this theory were tested. In this sense, two studies were carried out. Study 1 tested the content hypotheses and structure of values, considering a sample of 34,020 participants from all five regions of Brazil. They had a mean age of 26 years, being equally distributed by gender. In order to test these hypotheses, the sample was divided by region: North (n = 2328), Northeast (n = 17,431), Midwest (n = 2735), Southeast (n = 8554) and south (n = 2919). Initially, the content hypothesis was verified using confirmatory factor analysis (AFC), assuming that the 18 values could be represented in six values subfunctions (original model), confronting it with alternative factor structures (uni, bi, tri and pentafactorial). Regardless of region, the original model was the most adequate, with fit indexes acceptable (GFI, RMSEA). Subsequently, it was tested the structure hypothesis by confirmatory (Proxscal) multidimensional scaling (MDS), adopting the Tucker s Phi as an indicator of model fit. Consistently, in the five regions this value was above the recommended (0.90), indicating that the values could be represented in a space 3 (type of orientation: personal, social and central) x 2 (type of motivation: materialistic and idealistic). Study 2 aimed to replicate these findings, considering a total sample of 4,890 participants, whose mean age was 24.2 years, most female (57.7%), distributed in 12 countries: Germany (n = 156) , Argentina (n = 406), Brazil (n = 1,235), Colombia (n = 230), Spain (n = 874), Philippines (n = 279), Honduras (n = 199), England (n = 298); Israel (n = 167), Mexico (n = 274), New Zealand (n = 257) and Peru (n = 615). In the case of the content hypothesis, were tested by ACF the original model (hexafatorial) and alternatives (uni, bi, tri and pentafactorial), confirming in seven countries (Germany, Brazil, Spain, England, Israel, New Zealand, and Peru) better adequacy of the original model (Δχ ²; ECVI); in the other five countries (Argentina, Colombia, Philippines, Honduras and Mexico) the best models were the penta and hexafatorial, which did not differ between each other. In addition, it was tested the factorial invariance of the original model (hexafatorial), which gathered the configural, metric and structural invariance properties. As for the structure hypothesis, in all countries the fit indicator (Tucker's Phi) was adequate (φ ≥ 0.93), allowing to conclude that the values are configured in a 3 x 2 space, as theorized. It was sought to determine whether this structure remained equivalent across countries, by Generalized Procrustes Analysis (GPA), which allowed proving that the structure was similar in through the different countries (total adjustment greater than 0.90, average values of φ and Raw Stress of 0.94 and 0.11, respectively). It was concluded that, besides theoretically grounded, integrative and parsimonious, the functional theory of human values gathers empirical evidence of its suitability in Brazil and in other countries. Therefore, it can be properly used to understand human values and its correlates.